ISOLATION, PURIFICATION, AND CHARACTERIZATION OF BOVINE TENDON COLLAGEN AND ANALYSIS OF GLYCINE, PROLINE, AND HYDROXYPROLINE BY HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY-FLUORESCENCE - Yulianti, Dwi; ., Harmita; Rukmana, Taufiq Indra (International Journal of Applied Pharmaceutics, 2018)
Objective: In this study, collagen isolated from bovine tendon was purified and characterized, and the optimum conditions for analysis of glycine, proline, and hydroxyproline were determined. Methods: The collagen isolation process used 0.1 N NaOH as a pretreatment, 0.5 M acetic acid in the extraction, 0.9 M NaCl in the salting-out step, centrifugation and dialysis for purification, and freeze-drying as the final step. The characterization of the collagen included analysis of the organoleptic properties, pH, moisture content, viscosity, and ash content. A Fourier-transform infrared (FTIR) spectroscopy analysis and Casson's trichrome staining were also performed. The collagen was hydrolyzed in 6 N HCl for 24 h and derivatized using 9-fluorenylmethoxycarbonyl chloride. The optimum condition was conducted from the optimal wavelength, selection of mobile phase composition, and flow rate. Results: The average content was 11.867±0.20% for glycine, 33.247±0.20% for proline, and 10.51±0.23% for hydroxyproline. The optimum condition analysis for collagen was achieved by high-performance liquid chromatography (HPLC) with a C18® column and a fluorescence detector (excitation: 265 nm and emission: 320 nm) with mobile phase acetate buffer (pH 4.2):acetonitrile (55:45), and the flow rate was 0.8 mL/min. Conclusion: The collagen isolated from bovine tendon was obtained at a yield of 0.690%, and the identity was confirmed by FTIR functional group analysis and Casson's trichrome staining. The HPLC conditions using a fluorescence detector for analysis of glycine, proline, and hydroxyproline concentrations in the bovine tendon collagen were optimized. The analysis of amino acids gave the average levels of 33.247±0.20% for glycine, 11.867±0.20% for proline, and 10.51±0.23% for hydroxyproline.